Soft Materials Derived From Bile Acid Analogues - Bhat, Shreedhar (2009)
Chapter 1. Introduction This chapter is an overview on the literature of self-association of small organic molecules. The chapter is presented in four parts. First, an introduction to aggregation of small molecules is given with the emphasis on micelles and gels(Parts 1 and 2) In part 3, a short overview is given on bile acid based aggregates and their applications. Lastly, the content of the thesis is outlined. Chapter 2. Solution properties of novel cationic bil salts: A structure-aggregation property study Scheme 1: Structures of Cationic bile salts(Refer PDF File) Bile Salts are biosurfactants and they are known to form micelles in aqueous medium. We studied the micellar properties of cationic bile salts(Scheme 1) and compared with their natural (anionic) counterparts. A serendipitous discovery of the gelation of a cationic bile salt(4) led us to investigate the aggregation properties of this new class of cationic hydrogelators. This chapter highlights the recent efforts on the study of side chain structure-aggregation property relationship of cationic bile salts. Bile acid analogues with a quaternary ammonium group(Scheme 1, compounds 2, 3, 4, 6, 8 and 12) on the side chain were found to efficiently gel aqueous salt solutions. Some of the cationic bile salts gelled water alone and many of them gelled aqueous salt solutions even in the presence of organic co-solvents(≤ 20%) such as ethanol, methanol, DMSO and DMF. A strong counter ion dependent gelation was observed. These gels showed interconnected fibrous networks. Unlike natural anionic bile salt gels(reported for NaDC, NaLC), the cationicgels reported here are pH independent. Cationic gels derived from DCA showed more solid-like rheological response compared to natural NaDC gels studied earlier by Tato et al. A strong structure(side-chain) andcounter-ion dependent flow of the cationic bile salt gels was seen. Chapter 3. Applications of cationic bile salts and their aggregates Cationic bile salts are useful in many ways. We have studied some of the applications of cationic bile salts(discussed in chapter 2) and their aggregates in this chapter. The chapter is presented in three parts. Part 1. Interaction of Cationic bile salts and DNA The bile acid amphiphilicity is believed to help the DNA binding process of polyamines. This has prompted us to study the DNA-bile salt binding interaction of bile salts. The binding of cationic bile salts has been expressed in terms of C50 values, which were determined from the plot of fluorescence of ethidium bromide bound DNA vs. bile salt concentration(Fig 1) The C50 values for cationic bile salts were estimated to be about 1.2 mM. Fig1: A plot of fluorescene of ethidium bromide bound DNA against bile salt concentration (Refer PDF File) Part 2. Cholesterol solubilization and crystallization studies in aqueous bile salt solutions. Dihydroxy bile salt micelles are well known for cholesterol dissolution(e.g. UDCA and CDCA). We studied the dissolution of cholesterol in the cationic bile salt micelles(of 21-25) and the results are discussed in this part. Scheme 2: Cationic bile salt chlorides studied for cholesterol dissolution (Refer PDF File) A powder dissolution method was used to study the solubility of anhydrous cholesterol in cationic bile salt solution. These cationic bile salt micelles can dissolve cholesterol to the same extent as the taurine conjugates of bile acids, but lesser than the natural anionic bile salts(Fig.2) Addition of PC(Phosphatidylcholine) to cationic bile salt micelles enhanced the micellar cholesterol solubilization. Fig 2:Cholesterol dissolution in cationic bile salt solutions(Refer PDF File) The crystal nucleation time of cholesterol did not change significantly by adding 5-30 mM of the cationic bile salts. The bile salt analogues did, however, attenuate cholesterol crystallization to a similar extent at all concentrations studied. All these effects wer comparable to those fo cholic acid. Part 3. Hydrogels as a reaction vessel for photodimerization Bile salt micelles have been shown to control the product selectivity in photochemical reactions. The dynamic nature of the bile salt micelles results in differential effects on reaction selectivity. The photodimerization of acenaphthylene(sheme 3) was studied in micellar and hydrogel medium(e.g. NaDC, 22, 28, etc.) The ratio of anti- to synphotodimer was found to be greater in gel bound state than in solution. Substitution on the CAN ring did not show larger variation on the product distribution from solution gel. Scheme 3: Photodimerization of acenaphthylene(Refer PDF File) Chapter 4. Bile acid derived sulfur analogues in designing novel materials. Part 1. A simple approach towards nanoparticle-gel hybrid material. Scheme 4: Scheme for the synthesis of thiols derived from bile acids (Refer PDF File) Our interest in bile acid based gelator molecules led us to explore the synthesis and properties of bile analogues with the side chain carboxylic acid replaced by a thiol(Scheme 4) to stabilize metal NPs. We reasoned that the specific self-aggregation modes of facially amphiphilic bile units would enable a metal NP capped by such a thiol to “lock” onto a gel fiber derived from a structurally related gelator molecule. AuNPs stabilized by 38-40 were obtained by the NaBH4 reduction of homogeneous methanolic solutions of the thiol and gold salt. These steroid capped nanoparticles were found to stay dispersed in a gel of 28, thus providing a simple approach to obtain gel-nanoparticle hybrid. A photograph of the hybrid material and their morphology are shown in Fig 3.(Refer PDF File) Chart 1: Structure of the gelator used for designing a hybrid material(Refer PDF File) Part 2. Gelation of aromatic solvents using sulfur analogues of bile acid A few of the sulfur derivatives were serendipitously fouond to gel organic solvents (Fig 4). Thiol 38 formed stable gels at room temperatures while the disulphide 36 formed stable gels below 5º C. The aggregation properties, morphology, and the melting profiles of gels of disulfides and thiols derived from bile acids have been highlighted in this part. Fig 4: A photograph of the gels derived from 38(Refer PDF File) (For Figures and Molecular Formula Pl refer the Original Thesis)